INNOVATION OF KEMUHAMMADIYAH AL – ISLAM LEARNING AT MUHAMMADIYAH MOYUDAN SMP DURING THE COVID-19 PANDEMIC: INOVASI PEMBELAJARAN AL – ISLAM KEMUHAMMADIYAHAN DI SMP MUHAMMADIYAH MOYUDAN PADA MASA PANDEMI COVID-19 - Aisyah Ayun Khoirurrizki (Yayasan Hurriah, Banda Aceh, 2022)
The purpose of this study was to find out the innovations of Al Islam and Kemuhammadiyahan learning that were applied at SMP Muhammadiyah 1 Moyudan during the covid-19 pandemic. In the process of this research using descriptive qualitative techniques, with interviews, observations, photos and other learning platforms. The results show that there are several innovations applied by educators in the teaching and learning process during the pandemic. The innovations implemented at SMP Muhammadiyah 1 Moyudan are the presentation of learning with multimedia that utilizes the google classroom application, learning media videos and WAG, giving challenges to students and parents with the method of connecting paragraphs or letters, and implementing activity-based learning evaluations by creating independent and adaptable to new situations. The obstacles experienced during the learning process during the COVID-19 pandemic, among others, lack of understanding of ICT for parents and students, internet network problems, difficulties for educators to monitor the overall progress of students and delays in collecting assignments.